2009
DOI: 10.1097/mcg.0b013e31815591f7
|View full text |Cite
|
Sign up to set email alerts
|

Functional Dyspepsia

Abstract: The symptom-based Rome classification of functional dyspepsia does not lead to an easily applicable and consistent system that is useful in clinical practice or scientific research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…However, not every patient fits perfectly into each category and therefore, results may not accurately correspond to the patient pool presenting in the clinics. [8] The present study is the direct evaluation of discriminative value of Rome III questionnaire for FD in clinical setting. Our data suggests that Rome III questionnaire for FD was able to correctly place patients with dyspeptic symptoms into the FD category two out of three times in a clinical setting when this criteria was applied to patients with uninvestigated dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
“…However, not every patient fits perfectly into each category and therefore, results may not accurately correspond to the patient pool presenting in the clinics. [8] The present study is the direct evaluation of discriminative value of Rome III questionnaire for FD in clinical setting. Our data suggests that Rome III questionnaire for FD was able to correctly place patients with dyspeptic symptoms into the FD category two out of three times in a clinical setting when this criteria was applied to patients with uninvestigated dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies have provided indirect and mixed evidence on the dimensional or categorical nature of FD. Studies in healthcare‐seeking samples showed major overlap between EPS and PDS subgroups, pointing toward a dimensional structure of FD, whereas studies in population‐based samples indicated a good separation of both subgroups, suggesting a categorical structure . Studies on differential involvement of genetic polymorphisms and pathophysiological mechanisms, including gastric sensorimotor function, immune function, Helicobacter pylori infection and psychobiological processes in both subgroups have also yielded mixed results .…”
mentioning
confidence: 99%
“…Studies in healthcare-seeking samples showed major overlap between EPS and PDS subgroups, pointing toward a dimensional structure of FD, whereas studies in population-based samples indicated a good separation of both subgroups, suggesting a categorical structure. [8][9][10][11] Studies on differential involvement of genetic polymorphisms and pathophysiological mechanisms, including gastric sensorimotor function, immune function, Helicobacter pylori infection and psychobiological processes in both subgroups have also yielded mixed results. 2 Finally, confirmatory factor analyses (CFA) on dyspepsia symptom questionnaires both in the general population and in tertiary care have confirmed the existence of separate but correlated 'EPS', 'PDS', and 'nausea/vomiting' factors.…”
mentioning
confidence: 99%
“…The inclusive definition of dyspepsia used in the LDQ, which include symptoms of GERD as well, may appear to conflict with the Rome process [ 32 ]. However, the Rome definition of dyspepsia, and its requisite of excluding any symptoms of GERD, has been criticised for excluding many patients with genuine FD in both Asian [ 33 ] and non-Asian communities [ 34 ]. It has even less applicability for uninvestigated dyspepsia in the community, where both reflux symptoms and epigastric pain commonly coexist.…”
Section: Discussionmentioning
confidence: 99%